(untitled) (Orinoquia, 2020)
Prochilodus mariae (bocachico llanero or coporo) is amongst the most important fish in the Meta River (a major left tributary of the Orinoco River); along with being the largest of the Prochilodus species in the river basin, flannel-mouth characiforms contribute greatly to the dynamics of the region’s food chain and fisheries. This work was aimed at assessing Prochilodus mariae post-larvae feeding habits during their first thirty days of exogenous feeding until the beginning of the alevin stage. Simulations were made in the Instituto de Acuicultura de los Llanos (IALL) facilities’ earthen fish ponds to closely resemble the fishes’ natural annual water and feeding conditions. The ponds had been organically fertilised with cattle manure and hay and were then periodically inundated and drained to simulate the Meta River’s tributaries natural/annual floodplains or areas that are periodically inundated by high water levels. The ponds were stocked with larvae obtained by artificial spawning at twenty larvae/m2 density when around 80% of their yolk sacs had been absorbed. Post-larvae and pond water samples containing zooplankton and phytoplankton were collected at 8 am every other day for 30 days and fixed in 4% buffered formalin. Seven post-larvae/pond stomach/gut contents (frequency of fullness index - FI) were analysed from 156 specimens divided into size intervals ranging from 6-8.99, 9-17.99, 18-26.99, 27-35.99, 36-44.99 and 45-47.99 mm in length. Food items’ frequency of abundance (i.e. supply) in the pond water and periphyton were estimated. First-size interval post-larvae explore periphyton-related organisms for their food source (mainly bacteria, protozoans and algae). This first sampling was characterised by 66.7% of the post-larvae having empty stomachs. Second-size interval post-larvae FI tended reflect the consumption of pelagic organisms, having a preference for microcrustaceans (cladocerans and copepods). The longest alevins (45-47.99 mm long) started consuming detritus (particulate organic matter, bacteria and fungi) and other forms of phytoplankton close to the sides and bottom of the fishponds.